Barriers to Women’s Political Leadership in Pakistan: Analyzing Cultural, Institutional, and Religious Challenges in Achieving Gender Equality in the Political Sphere - Kainaat , Farah; Ullah, Dr. Hafiz Ahmed; Wajid, Hassan; Sarwar, Dr. Muhammad (Al Khadim Research Journal of Islamic Culture and Civilization, 2024)
Women’s involvement in politics promotes social growth, democratic advancement, and gender equality. This article’s goal is to shed light on Pakistan’s political culture in order to comprehend the obstacles that stand in the way of women’s advancement in political leadership, including institutional impediments, religious influences, cultural norms, values, and beliefs. The history of Pakistan, where female political figures served the country and introduced laws pertaining to women, demonstrates the value of female leadership. Women’s roles were disregarded and undervalued in Pakistani politics’ gloomy democratic history. The papers do, however, draw attention to past patterns, mistakes, and achievements. In order to better understand the potential and problems involved, the secondary sources are analyzed using an analytical research methodology with a qualitative approach. Thus, the study offers a detailed analysis of Pakistani political culture and concludes that the primary cause of women’s underrepresentation is the country’s political system. The report makes suggestions and exhorts governments, the public sector, and other interested parties to collaborate in order to give gender equality top priority and enable women to have a greater say in how the nation is shaped in the future.